The collected works (gsuṅ ʼbum) of Spyan-sṅa Blo-gros-rgyal-mtshan of Rgya-ma Rin-chen Sgaṅ - Blo-gros-rgyal-mtshan, Spyaṅ-sṅa, 1402-1471 (Gedan sungrab minyam gyunphel series ;, 1983)
Writings on Buddhism by a scholar of the Gelukpa tradition.